Evolución del índice de masa corporal, hematocrito y presión arterial en estudiantes de Medicina: Evolution of body mass index, hematocrit and blood pressure in medical students - Peña-Delgado, Cassandra Danalis (2022)
Objetive: To describe the evolution of body mass index, hematocrit and blood pressure in medical students. Methods: Longitudinal and retrospective study. 77 clinical histories were analyzed in medical students, who were attended in service Bienestar Universitario of the UNT, from first academic year (2013) to sixth academic year (2018). Was evaluated the mean and standard deviation, and if exists difference according gender and the totality of students, through statistics test t student, p < 0.05. Results: 29.87% were women and 70.13% men. The mean and standard deviations were respectively: BMI (Body mass index, kg/m2) 23.26 (DE: 3.99) and 24.85 (DE: 3.87), SBP (mmHg) 113.39 (DE: 11.75) and 117.70 (DE: 13.40), DBP (mmHg) 69.90 (DE: 10.36) and 69.19 (DE: 8.10), hematocrit in female group 39.48% (DE: 2.91) and 39.17% (DE: 2.85), hematocrit in male group was 46.74% (DE: 2.55) and 45.43% (DE: 2.86). Mean differences between first and sixth year; in all students, in BMI and SBP were significant (p<0.05), not in DBP; in female gender changes in BMI was significant (p<0.05), but not SBP, DBP and hematocrit; and in male gender BMI, hematocrit and SBP were significant, but not DBP. Conclusion: Over the course of 6 years of study, BMI and SBP in medical students increase; hematocrit in male gender decrease and in female gender doesn’t change.